Kelayakan Ekonomis Penerapan Teknologi Pengolahan Jeruk Nipis Sebagai Bahan Dasar Sabun Cuci Skala UMKM di Kecamatan Kuala Kabupaten Nagan Raya - Safrika, Safrika; Darma, Rizki Muthiara; Atikah, Qhisthina; Malia, Rezqi; Maliza, Noer Octaviana; Bagio, Bagio (Jurnal Teknologi Pengolahan Pertanian, 2025)
This study analyzes the feasibility of a lime-based dishwashing soap business developed by the Women's Entrepreneur Group (KWW) Makmue Beujaya in Kuta Makmue Village, Nagan Raya Regency. Using a case study approach and quantitative analysis, the research examines production aspects, costs, and business profitability. The results show that this business has a Revenue-Cost Ratio (R/C Ratio) of 1.94, indicating excellent financial feasibility according to UNIDO standards (2022). Profit per production cycle reaches IDR 581,000 with a 48.4% profit margin, significantly exceeding the average for similar MSMEs (25-30%) based on data from the Ministry of Cooperatives and SMEs (2023). The cost structure is dominated by variable costs (96.9%), primarily for packaging materials (40.2%) and texapon (30%). Further analysis reveals that this business model is not only financially viable but also has development potential through production scale-up and supply chain optimization. These findings make an important contribution to the development of micro-enterprises based on local commodities in rural areas.